Environmental Factors, Occupational Hazards, and Seasonal Changes: Unveiling the Triggers of Atrial Fibrillation - Hamad, Adel Khalifa Sultan (Cardiovascular & Haematological Disorders - Drug Targets, 2024)
IntroductionAtrial Fibrillation (AF) is the most common cardiac arrhythmia in the world, with a lifetime risk of 26% for men and 23% for women. AF is a prevalent cardiac arrhythmia that is more common with increasing age. Globally, around 33.5 million people are estimated to have AF, which is anticipated to rise as the population ages. Although effective therapeutic methods exist, they are costly for the healthcare system.MethodsThe search was conducted across multiple databases, including Medline, PubMed, and Google Scholar, as well as through manual searches of recognized publications and their bibliographies. Identifying modifiable risk factors for AF and implementing appropriate preventative measures may significantly improve public health and reduce healthcare costs. The development of AF has been reported to be associated with various causes, including electrical and structural changes in the atrial tissue.ResultsThis article has reviewed how environmental factors, occupational hazards, and seasonal variability can affect AF. The incidence and prevalence of AF have been increasing, leading to a high lifetime risk for individuals. The available evidence indicates that seasonal variation, environmental factors, such as noise and air pollution, type of job, and altitude are all associated with an increased risk of developing AF. Although the exact mechanisms underlying these associations remain unclear, it is likely that a combination of factors, including changes in autonomic tone, inflammation, and oxidative stress, play a role.ConclusionThis review has highlighted the significance of assuming the role of environmental and occupational factors in the development of AF.
Keywords: environmental factors